Can Mindfulness Meditation Improve Short-term and Long-term Academic Achievement in a Higher-education Course?. Issue 3 (3rd July 2019) - Baranski, Michael F. S.; Was, Christopher A.
Abstract: Mindfulness meditation involves focusing one's attention on the present moment in a non-judgmental way. Several recently published investigations have demonstrated that a brief session of mindfulness meditation, practiced before a higher-education course lecture, can improve performance on a quiz over lecture content given immediately following the lecture. It is less clear how mindfulness meditation, practiced before multiple course lectures, impacts performance on quizzes over time as well as on a cumulative exam over all lecture contents. The present experiment compared a mindfulness meditation group to an active control group; each practiced 6 min of mindfulness or relaxation prior to seven course lectures. Following each lecture, a quiz was given over lecture contents to measure short-term academic achievement. A cumulative exam was later given over all lecture content to measure long-term academic achievement. In contrast to prior published investigations, there were no effects of mindfulness meditation on academic achievement. Given these promising yet inconsistent effects, future work should explore the moderators (i.e., individual differences; duration, frequency, and style of meditation practice) of mindfulness meditation's salutary benefits.